2017
DOI: 10.1111/jpn.12750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed supplementation with a copper‐glycine chelate and copper sulphate on selected humoral and cell‐mediated immune parameters, plasma superoxide dismutase activity, ceruloplasmin and cytokine concentration in broiler chickens

Abstract: SummaryThe varied bioavailability and different effects of organic forms of copper on the immune system of poultry have prompted the search for new feed additives based on copper compounds containing modified chelate complexes. The aim of the study was to determine the effect of inorganic and organic forms of copper on selected parame- K E Y W O R D Schicken, copper-glycine chelate, cytokine expression, flow cytometry, superoxide dismutase activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 50 publications
(58 reference statements)
7
20
2
Order By: Relevance
“…The present results agreed with those reported by Jarosz et al (2018) who reported that SOD activity increased by feeding broiler chickens on diets rich in copper sulphate. It is well-known that Cu has the ability to regulate SOD activity in the tissues and body fluids of both growing and aged animals (Surai 2016).…”
Section: Antioxidants Responsesupporting
confidence: 94%
“…The present results agreed with those reported by Jarosz et al (2018) who reported that SOD activity increased by feeding broiler chickens on diets rich in copper sulphate. It is well-known that Cu has the ability to regulate SOD activity in the tissues and body fluids of both growing and aged animals (Surai 2016).…”
Section: Antioxidants Responsesupporting
confidence: 94%
“…Copper plays an important role in immune response processes (Chatterjee et al, 2009;Jarosz et al, 2018). Copper deficiency is associated with developmental disturbances of the lymphoid organs, a decrease in the percentage of T cells, impairment of their maturation in the spleen and reactivity to mitogens, and a reduction in antibody synthesis and the phagocytic index of cells (Das et al, 2014;Hong et al, 2002;Jarosz et al, 2018;Lim & Paik, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Copper plays an important role in immune response processes (Chatterjee et al, 2009;Jarosz et al, 2018). Copper deficiency is associated with developmental disturbances of the lymphoid organs, a decrease in the percentage of T cells, impairment of their maturation in the spleen and reactivity to mitogens, and a reduction in antibody synthesis and the phagocytic index of cells (Das et al, 2014;Hong et al, 2002;Jarosz et al, 2018;Lim & Paik, 2006). Copper deficiency also delays the acute phase response, which is linked to impairment of synthesis of acute phase proteins (APP) such as ceruloplasmin, cytokine synthesis, and the generation of reactive oxygen species during phagocytosis (Das et al, 2014;Jarosz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations